The Relationship Between Health Education and Community Compliance with Clean and Healthy Living Behavior (PHBS) in Ngali Village, Bima Regency - Mutmainni Mutmainni (LPPM Universitas Dhyana Pura, 2026)
Community compliance is an important indicator of the success of health promotion programs. One factor that may influence compliance is health education, which aims to improve people's knowledge, attitudes, and healthy behaviors. This study aimed to determine the relationship between health education and community compliance. This research employed an analytical observational design with a cross-sectional approach. The study involved 60 respondents selected using total sampling. Data were collected using structured questionnaires and analyzed using univariate and bivariate analyses. The Chi-Square test was used to determine the relationship between health education and community compliance with a significance level of α = 0.05. The findings showed that 32 respondents (53.3%) had received health education, while 28 respondents (46.7%) had not. Most respondents had a moderate level of community compliance (51.7%). The Chi-Square analysis demonstrated a statistically significant relationship between health education and community compliance (p = 0.002). Respondents who received health education had a higher proportion of high compliance (43.8%) than those who did not receive health education (10.7%). Health education is significantly associated with community compliance. Continuous and comprehensive health education programs are recommended to improve public knowledge and encourage positive health behaviors, thereby increasing community compliance with health recommendations.